Mass ordering of spectra from fragmentation of saturated gluon states in high-multiplicity proton-proton collisions - Schenke, Björn Peter; Schlichting, Sören; Tribedy, Prithwish; Venugopalan, Raju (Physical review letters, 2016)
The mass ordering of mean transverse momentum ⟨pT⟩ and of the Fourier harmonic coefficient v2(pT) of azimuthally anisotropic particle distributions in high energy hadron collisions is often interpreted as evidence for the hydrodynamic flow of the matter produced. We investigate an alternative initial state interpretation of this pattern in high-multiplicity proton-proton collisions at the LHC. The QCD Yang-Mills equations describing the dynamics of saturated gluons are solved numerically with initial conditions obtained from the color-glass-condensate-based impact-parameter-dependent glasma model. The gluons are subsequently fragmented into various hadron species employing the well established Lund string fragmentation algorithm of the pythia event generator. We find that this initial state approach reproduces characteristic features of bulk spectra, in particular, the particle mass dependence of ⟨pT⟩ and v2(pT).
Gesehen am 13.05.2020